1989
DOI: 10.1136/oem.46.5.334
|View full text |Cite
|
Sign up to set email alerts
|

Job demands, job decision latitude, job support, and social network factors as predictors of mortality in a Swedish pulp and paper company.

Abstract: Three hundred and ninety one male employees aged 35-65 in a Swedish pulp and paper company were followed up for 22 years; 151 deaths were recorded by 31 December 1983. On the basis of data from 1961, indices for job decision latitude, job support, and other work related psychosocial factors were constructed as were five indices for non-work related social network factors. All indices were checked by life table analysis in respect of mortality. Job decision latitude and a combined index for job decision latitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 31 publications
0
23
1
Order By: Relevance
“…The demand/latitude model was also applied in a longitudinal study of 391 male employees of a Swedish pulp and paper company (Astrand et al 1989). With all cause mortality as the outcome and perceived measures ofjob characteristics, neither psychological nor physical job demands influenced mortality.…”
Section: Introductionmentioning
confidence: 99%
“…The demand/latitude model was also applied in a longitudinal study of 391 male employees of a Swedish pulp and paper company (Astrand et al 1989). With all cause mortality as the outcome and perceived measures ofjob characteristics, neither psychological nor physical job demands influenced mortality.…”
Section: Introductionmentioning
confidence: 99%
“…It is particularly known as a risk factor for cardiovascular disease (1)(2)(3)(4)(5)(6), hypertension (7)(8)(9), and arteriosclerosis (10)(11)(12). In research on the health effects of work stress, the demand-control model is well known, and Karasek et al (13,14) reported that high job strain, defined as a combination of high job demands and low job control, was related to an increased incidence of cardiovascular disease in populations in Sweden and the United States.…”
mentioning
confidence: 99%
“…First, previous studies (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) showing a positive association between job stress indices (ie, job demand, control, strain and support depending on the study) and CVD have been conducted extensively in Europe and the United States, but not in Japan, where the incidence of CVD and culture differ. Second, in these studies, the application of the Job Content Questionnaire with respect to CVD was limited by reliance on prevalence data (4,8,11,13).…”
mentioning
confidence: 99%